Strains of Mycobacterium tuberculosis differ in susceptibility to reactive nitrogen intermediates in vitro. - O'Brien, L (1994)
The effects on the viability of Mycobacterium tuberculosis strains and one Mycobacterium bovis strain from exposure to sodium nitrite for 24 h, in both neutral and acidic media, were tested. The in vitro resistance of mycobacteria to reactive nitrogen intermediates, generated at an acidic pH, was found to have a significant (P < 0.05) positive correlation to the virulence of strains in guinea pigs.